Relationship Between Foreign Direct Investment, Industrial Structure Optimization, and Green Full-Factor Productivity: Empirical Evidence From Changjiang Economic Area - Zhang, Huaping; Ren, Yuanyuan (Frontiers in Environmental Science, 2022)
By setting up an evaluation indicator system (EIS) containing bad outcomes for green full-factor productivity (GFFP), this work utilizes the super epsilon-based measure (Super EBM) model to assess the GFFPs of 11 regional-level administrative regions (regions) in the Changjiang Economic Area (CEA) from 2005 to 2019, and goes on to analyze the regional difference and spatial correlation between the regional GFFPs. On this basis, spatial measurement models were adopted to analyze how GFFP is affected by foreign direct investment (FDI), industrial structure optimization (ISO), and their cross term. The results show that: During the sample period, the GFFPs in the CEA exhibited large regional differences. Shanghai’s GFFP fell on the efficient frontier. This state was not achieved by any other region in the CEA, leaving a room for improvement. In general, most regions in the lower basin of the CEA had satisfactory GFFPs, while those in the middle and upper basin had general GFFPs. Besides, the GFFP trends were similar in the upper, middle, and lower basin of the CEA. Before 2010, the GFFPs in all three regions did not change significantly. After that year, the GFFPs in the three regions began to decline. During the sample period, the Global Moran’s I values of CEA GFFPs remained positive, and went through the test of significance in most years. Thus, the GFFPs were clustered prominently in space. Considering the results of spatial measurement models, the CEA GFFPs were significantly inhibited by FDI, and promoted by ISO; the cross term between FDI and ISO positively affected GFFP. Among the control parameters, economic growth and environment regulation clearly promote GFFP, urbanization level strongly inhibits GFFP, and energy structure does not significantly affect GFFP. The research results disclose the internal correlations between FDI and ISO in the transformation to green development: the benign interaction between FDI and regional ISO paves the way to green development for the CEA.